Pattern based optical memory in rubidium vapor - Korneev, Nikolai; Torres, Y. M. (Acta Universitaria, 2013)
We investigated the optical transverse pattern produced by counterpropagating two waves through a rubidium vapor cell in presence of a longitudinal magnetic field. A bistable behavior is observed. The optical switching process between two of these patterns is carried out using three different mechanisms: mechanical closing of a pump beam, modulation of a pump beam intensity and modulation of additional beam intensity. A rapid switching of less than 10 μs between patterns can be carried out with a 2 μw power beam.
Keywords: Array; Array